DETECTION OF EXTENDED SPECTRUM BETA LACTAMASES-PRODUCING KLEBSIELLA PNEUMONIAE ISOLATES IN CHRONIC OBSTRUCTIVE PULMONARY DISEASES PATIENTS - R, Shangamithra; R, Saraswathi; A, Anupriya; P, Chitra Rajalakshmi; J, Lalithambigai (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: Chronic obstructive pulmonary disease (COPD) is the leading cause of morbidity and mortality worldwide which includes chronic bronchitis and emphysema. 80% of acute exacerbation of COPD (AECOPD) are triggered by respiratory viruses, atypical bacteria, and aerobic Gram-positive and Gram-negative bacteria. The aim of our study was to analyze the prevalence and antimicrobial susceptibility testing of Klebsiella pneumoniae and detection of extended spectrum beta lactamases (ESBL)-producing K. pneumoniae isolates from COPD patients. Methods: Sputum samples received from seventy-five diagnosed cases of COPD from the department of General Medicine and Chest Medicine, TSRM MCH and RC, Trichy, from March 2022 to August 2022. Direct Gram stain was done for all sputum samples. The suitable sputum samples were cultured. The identification of organism and antimicrobial susceptibility testing was done by standard microbiological techniques. Results: Out of seventy-five cases, 64% were males and 36% were females. Forty-seven were sputum positive, and the prevalence of Gram- negative bacteria was 64%. K. pneumoniae was the most common bacteria isolated (42.2%), followed by Pseudomonas aeruginosa (15.5%). Antimicrobial susceptibility testing of K. pneumoniae was sensitive to imipenem (78.94%), aminoglycosides (78.94%), amoxycillin-clavulinic acid (63.15%), ciprofloxacin (57.89%), Piperacillin-Taxobactam (57.89%), and the phenotypic tests showed 13 (68%) isolates were ESBL producers. Conclusion: This study showed that K. pneumoniae and P. aeruginosa are the most common organisms associated with AECOPD and increased rate of ESBL producers were observed.